Relationship between Mother's Knowledge of Breastfeeding and Exclusive Breastfeeding for Nursing Mothers in the Operational Area of the Sudiang Primary Health Center - Wahyuni, Dian; Rosdianah; Asriani (Green Medical Journal, 2021)
Introduction: Exclusive breastfeeding is breastfeeding only in the first 6 months without drinks or other additional foods. There are several factors that influence breastfeeding behavior, one of which is the mother's knowledge. This research was conducted to determine whether there is a relationship between maternal knowledge and exclusive breastfeeding behavior Methods: This study used an analytic observational study design with a cross sectional approach. The sample of this research is breastfeeding mothers who have children aged 6-24 months in the working area of Sudiang Health Center. Samples were taken using purposive sampling technique with a total sample of 262 people. Data was collected by filling out questionnaires by respondents. Results: The results showed that mothers Introduction: Exclusive breastfeeding is breastfeeding only in the first 6 months without drinks or other additional foods. There are several factors that influence breastfeeding behavior, one of which is the mother's knowledge. This research was conducted to determine whether there is a relationship between maternal knowledge and exclusive breastfeeding behavior Methods: This study used an analytic observational study design with a cross sectional approach. The sample of this research is breastfeeding mothers who have children aged 6-24 months in the working area of Sudiang Health Center. Samples were taken using purposive sampling technique with a total sample of 262 people. Data was collected by filling out questionnaires by respondents. Results: The results showed that mothers who have high knowledge and provide exclusive breastfeeding are more than 56.1%. Analysis of the two variables shows the value of p = 0.000. Statistically, there is a significant relationship between maternal knowledge and exclusive breastfeeding behavior Conclusion: The conclusion of this research is that there is a relationship between maternal knowledge and the behavior of exclusive breastfeeding in the working area of the Sudiang Health Center. Keywords: Mother's Knowledge; Breastfeeding; Exclusive Breastfeeding who have high knowledge and provide exclusive breastfeeding are more than 56.1%. Analysis of the two variables shows the value of p = 0.000. Statistically, there is a significant relationship between maternal knowledge and exclusive breastfeeding behavior Conclusion: The conclusion of this research is that there is a relationship between maternal knowledge and the behavior of exclusive breastfeeding in the working area of the Sudiang Health Center. Keywords: Mother's Knowledge; Breastfeeding; Exclusive Breastfeeding